Transformation of Islamic Character Values in the Bugis Song "Ininnawa Sabbarae" into Students’ Creative Literary Works - Nasirah Nasirah (Journal of Indonesian Islamic Studies, 2026)
This study investigates the transformation of Islamic character values embedded in the Bugis traditional song Ininnawa Sabbarae into students’ creative literary works. The study is grounded in the assumption that local cultural texts not only preserve cultural heritage but also function as effective media for character education. The research aims to identify the Islamic character values contained in the song and analyze how these values are transformed into students’ literary creations. Employing a qualitative descriptive approach, the study involved 15 undergraduate students enrolled in a Creative Writing course. Data were collected through classroom observations, document analysis of 23 literary works consisting of poems, short stories, and monologues, as well as semi-structured interviews. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing. The findings reveal that the dominant Islamic character values represented in Ininnawa Sabbarae include sabr (patience), istiqamah (perseverance), ikhtiar (continuous effort), optimism, and orientation toward goodness (al-khair). These values were transformed into literary expressions through metaphorical language, emotional imagery, narrative conflicts, and contextual life experiences. Students did not merely reproduce the song’s messages but actively reconstructed them according to their personal experiences, social realities, and religious reflections. The transformation process functioned not only as a literary activity but also as a medium for internalizing Islamic character values and preserving Bugis cultural heritage. This study contributes to the discourse on Islamic character education by demonstrating how local wisdom can be integrated into creative writing instruction to strengthen students’ moral awareness, cultural identity, and literary creativity in higher education.